The dialectic between the act of writing and the act of reading - Zagir, Nazyehaa (Arab Journal for Sciences and Research Publishing, 2015)
This study describes the problems result of the relationship between the act of writing and the act of reading it is not easy to understand because it requires an intelligent and subtle reader to resist into undermined text traps , these traps that start from the shape of the text, it is difficult to find away to break this kind of fortress ( text form ) Because we believe that the author has a absolute power on the form he must give her a text ignoring the subtlety and insight of mind’s reader he will surprise by an unexpected reading with a formation of a new form other than that it had proposed to the readers.